2020
DOI: 10.1016/j.oceaneng.2020.107428
|View full text |Cite
|
Sign up to set email alerts
|

Scale effect on ship resistance components and form factor

Abstract: To design eco-friendly ships, the hydrodynamic behaviour of the hull has to be estimated precisely.The first and foremost one is the ship resistance, which is closely related to the energy efficiency of the ship. Different extrapolation methods, based on different assumptions, have been used to predict the full-scale ship resistance from model-scale experiments. In this manner, it is important to understand the scale effect on the individual ship resistance components. In this study, URANS CFD simulations of K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 25 publications
2
25
0
5
Order By: Relevance
“…The previous CFD studies presented by Raven et al [42], Wang et al [25], Dogrul et al [26], Korkmaz et al [27], Terziev et al [24], Van et al [43], and Korkmaz et al [28] supported the existence of speed dependency for the form factors even though this should not be the case according to the hypothesis of Hughes [6]. Therefore, regardless of the choice of the CFD code, numerical methods, and settings, the choice of speed that the double body computations are performed for will have a significant impact on the CFD based form factors when the ITTC-57 model to ship correlation line is used.…”
Section: Variation Of the Model Scale Speedmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous CFD studies presented by Raven et al [42], Wang et al [25], Dogrul et al [26], Korkmaz et al [27], Terziev et al [24], Van et al [43], and Korkmaz et al [28] supported the existence of speed dependency for the form factors even though this should not be the case according to the hypothesis of Hughes [6]. Therefore, regardless of the choice of the CFD code, numerical methods, and settings, the choice of speed that the double body computations are performed for will have a significant impact on the CFD based form factors when the ITTC-57 model to ship correlation line is used.…”
Section: Variation Of the Model Scale Speedmentioning
confidence: 99%
“…As identified by the ITTC Specialist Committee on the Combined CFD/EFD Methods, if a part of the model testing or extrapolation procedure causes higher uncertainty than the numerical uncertainty and modeling errors of the CFD applications, the accuracy is expected to increase. In the 1978 ITTC Performance Prediction method [20], the form factor approach is identified as a major uncertainty source due to its determination method, i.e., the Prohaska Method [5], and the scale effects when the ITTC-57 model to ship correlation line is used [21][22][23][24][25][26][27][28]. The study performed by Wang et al [29] showed that when the Prohaska Method is replaced by CFD based form factors in the ITTC-78 Power Prediction Method, the sea trials correlated better for a ship.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it should be pointed out that the identification methods used need not be restricted to the suggested model structures or the utilised vessel and its actuators. For example, a similar approach could be applied to the real-size Watertruck + vessels, which would eliminate the scale effects [73] which would occur when one extrapolates the presently identified models. It is noteworthy that the small scale factor of eight should help in decreasing these scale effects [74].…”
Section: Discussionmentioning
confidence: 99%
“…Figure 4 depicts the computational domain and the boundary conditions of the Wigley hull simulations used in this study. The computational domain size was chosen to be similar to that used by Dogrul et al [31]. The velocity inlet boundary conditions were used for the inlet, top and bottom boundaries while the pressure outlet boundary condition was used for the outlet boundary.…”
Section: Geometry and Boundary Conditionsmentioning
confidence: 99%